Report from the PhD Symposium at XP2013 – An Adaptive Experiment in Feedback - Hunt Johanna; Akerele Olumide; Juhola Tomi; Waterman Michael (ACM New York, 2022)
In this paper, we describe the PhD Symposium organized as a part of the 14th International Conference on Agile Software Development (XP2013). The Symposium was run with an experimental adaptive structure and was divided into two workshops distributed across the conference as well as individual sessions during the conference. The activities of the second workshop were adapted based on the learning needs of the attendees. In this report we describe the structure of the two scheduled workshops, the activities conducted both during and between them, and evaluate the outcome of this Symposium format.